2022
DOI: 10.7570/jomes21088
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Taurine on Metabolic Parameters in Animals and Humans

Abstract: Taurine (2-aminoethanesulfonic acid) is a non-essential amino acid mainly obtained through diet in humans. Despite the lack of research on the health effects of taurine in animals and humans, it is widely used as a dietary supplement. Evidence from human and animal studies indicates that taurine is involved in conjugation of bile acids and regulation of blood pressure and has anti-oxidative, anti-inflammatory, and anti-obesogenic properties. Taurine can benefit both human and non-human animal health in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…As a result, there is an increased energy demand or decreased energy production in these cells. These changes show that how taurine deficiency and subsequent detrimental changes in metabolism attenuate neutrophil function ( Richer et al, 2018 ; Schaffer and Kim, 2018 ; Tappia et al, 2018 ; Bae et al, 2022 ; Miyazaki et al, 2022 ).…”
Section: Metabolic Alterations In Innate Immune Cellsmentioning
confidence: 98%
“…As a result, there is an increased energy demand or decreased energy production in these cells. These changes show that how taurine deficiency and subsequent detrimental changes in metabolism attenuate neutrophil function ( Richer et al, 2018 ; Schaffer and Kim, 2018 ; Tappia et al, 2018 ; Bae et al, 2022 ; Miyazaki et al, 2022 ).…”
Section: Metabolic Alterations In Innate Immune Cellsmentioning
confidence: 98%
“…Collectively, it appears that a host of approved and experimental antidiabetic drugs impart at least some direct or indirect effects of islet cell plasticity. Indeed, even taurine, a semi‐essential ubiquitous amino acid shown to alleviate obesity and hyperglycaemia in humans, 160 seems to encourage α‐ to β‐cell transdifferentiation 161 . An exclusion from this list is the widely employed sodium‐glucose co‐transporter‐2 inhibitor, dapagliflozin, which did not alter islet cell plasticity in STZ‐induced diabetic mice 76 .…”
Section: Strategies To Utilize Transdifferentiation In the Generation...mentioning
confidence: 99%
“…Animal studies have shown that taurine has a strong anti-obesity impact, but the dosages employed to treat obese animals are not suitable for human intake as a nutritional supplement [ 10 ]. The fact that clinical research on humans has not been able to conclusively demonstrate taurine's ability to reduce obesity can be due to the lack of physiologically practical dose.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that clinical research on humans has not been able to conclusively demonstrate taurine's ability to reduce obesity can be due to the lack of physiologically practical dose. Due to their hereditary propensity to become obese and in response to consuming a high fat diet (HFD), C57BL/6J ob/ob mouse models are utilized to imitate obese conditions [ 10 , 11 ]. These ob/ob mice frequently experience pre-diabetic symptoms such as obesity, elevated blood triglycerides levels, and altered glucose homeostasis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%